Profiling students' critical thinking skills in the human digestive system - Lilan Dama; Nurul Fajryani Usman; Sabrina Yusuf (Universitas Negeri Jakarta, 2026)
Critical thinking is an important component in 21st-century Biology education, which demands the ability to critically analyze scientific concepts and information. However, students' critical thinking skills are still relatively low. This study aims to describe the profile of critical thinking skills of eleventh-grade students at a high school in North Sulawesi on the human digestive system. The method used is a quantitative approach with a descriptive design. The sample consisted of 19 randomly selected students. The research instrument was a test developed based on five critical thinking indicators according to Ennis, providing simple explanations, building basic skills, concluding, providing advanced explanations, and developing strategies and tactics. Data were analyzed descriptively quantitatively by looking at the percentage of achievement in each indicator. The results showed that most students' critical thinking skills were in the low category. As many as 74% of students were very low in providing simple explanations, and 89% were in the very low category in the advanced explanation indicator. The highest achievement only reached the sufficient category. These findings indicate that conventional Biology learning practices have not been able to encourage the development of critical thinking skills optimally. Therefore, this study emphasizes the importance of implementing profile-based diagnostic assessments and integrating active, contextual learning strategies that are oriented towards higher-order thinking skills in Biology learning.